Design and synthesis of low temperature printed metal oxide electronic devices - Carlos, Emanuel Abreu Antunes (2020)
Printed electronics have led to new possibilities in the development of low-cost and lowtemperature methods for materials production and processing. Inorganic oxide devices that are totally solution-processed offer an appealing approach, overcoming some limitations of organic electronics, such as performance and stability. Solution processes are simple and versatile however, there are still some drawbacks that need to be addressed. Currently, synthesis of these materials usually needs higher temperatures and longer annealing time which limits their use on flexible substrates being crucial for flexible and wearable device applications. In this thesis, a general overview is made to solution combustion synthesis (SCS) method to synthetize nanostructures, thin films and their application in thin film transistors (TFTs) with a low thermalbudget.Also,newstrategiestowardsprocessing ofsolution-basedmetaloxide TFTs such as, oxide synthesis, post deposition treatments, low temperature high emerging printing techniques are discussed. Relevantstepstoboost solution-basedmetaloxideTFTs are analysed,sincetheoptimizationof metal oxide (MO) thin films processed at low temperature until their printability in Roll-to-Roll (R2R) compatible techniques. To go even further some tests are performed to decrease the processing time required for the formation of MO thin films. To finalize, special attentionisgiven tosolution-basedmetaloxide resistiveswitchingdevices in which the resistive states are quite important to represent different logic states (e.g. binary code) being useful for many digital applications.